2020
DOI: 10.1021/acsnano.9b09871
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light-Triggered Nitric-Oxide-Enhanced Photodynamic Therapy and Low-Temperature Photothermal Therapy for Biofilm Elimination

Abstract: Photothermal treatment (PTT) involving a combination of therapeutic modalities recently emerged as an efficient alternative for combating biofilm. However, PTT-related local high temperature may destroy the surrounding healthy tissues. Herein, we present an all-in-one phototherapeutic nanoplatform consisting of l-arginine (l-Arg), indocyanine green (ICG), and mesoporous polydopamine (MPDA), namely, AI-MPDA, to eliminate the already-formed biofilm. The fabrication process included surface modification of MPDA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
389
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(424 citation statements)
references
References 65 publications
4
389
0
Order By: Relevance
“…Recently, photothermal treatment application based on hybrid PDA NPs consisting of l-arginine (l-Arg), indocyanine green (ICG), and mesoporous PDA (MPDA) was designed by Yuan et al as an alternative to eliminate bacterial biofilm ( Figure 8A) [132]. The synthesised particles displayed relatively uniform size distribution with a diameter of about 200 nm ( Figure 8B), optimal ICG loading efficiency of more than 90.0% was achieved, and the loading content was 9.0 µg ( Figure 8C-E).…”
Section: Biocompatibility Of Pda Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, photothermal treatment application based on hybrid PDA NPs consisting of l-arginine (l-Arg), indocyanine green (ICG), and mesoporous PDA (MPDA) was designed by Yuan et al as an alternative to eliminate bacterial biofilm ( Figure 8A) [132]. The synthesised particles displayed relatively uniform size distribution with a diameter of about 200 nm ( Figure 8B), optimal ICG loading efficiency of more than 90.0% was achieved, and the loading content was 9.0 µg ( Figure 8C-E).…”
Section: Biocompatibility Of Pda Npsmentioning
confidence: 99%
“…(E) UV/vis absorbance spectra of MPDA (0.1 mg mL −1 ), Arg, ICG (5 μg mL −1 ), and AI-MPDA NPs (0.1 mg mL −1 ). From reference [132] Reprinted with permission from the American Chemical Society.…”
Section: Biocompatibility Of Pda Npsmentioning
confidence: 99%
“…Besides the free form, MRAB also exists in the form of bio-lms. [32][33][34] In clinics, a large number of implantable medical device-caused bacterial infections are related to MRAB bio-lms. 35,36 Once the biolms are formed on the surface of implantable devices, they are difficult to eradicate due to the protection of the polymeric matrix in biolms.…”
Section: Bacterial Biolm Ablation and Inhibition Effects In Vitromentioning
confidence: 99%
“…In vivo results showed that MoS 2 -BNN6 with enhanced photothermal treatment/NO synergetic antibacterial function achieves >97.2% inactivation of bacteria within 10 min of NIR irradiation, and could also effectively repair wounds through the formation of collagen fibres and elimination of inflammation during tissue reconstruction. Similarly, Cai et al 28 presented an all-in-one phototherapeutic nanoplatform AI-MPDA, which includes L-arginine (L-Arg), ICG and mesoporous polydopamine (MPDA) ( Figure 13 A ). AI-MPDA not only generated heat but also produced ROS and catalyzed L-Arg to release NO under NIR irradiation, furthermore, the released NO significantly enhanced the therapeutic effects of photodynamic treatment and low-temperature photothermal treatment (≤45 °C), contributing to the elimination of bacterial biofilm.…”
Section: Combined Phototherapymentioning
confidence: 99%